2006
DOI: 10.1016/j.febslet.2006.01.048
|View full text |Cite
|
Sign up to set email alerts
|

The conserved Ala37 in the ERF/AP2 domain is essential for binding with the DRE element and the GCC box

Abstract: Four AP2/EREBP genes encoding putative ethyleneresponsive element binding factor (ERF)/AP2 domains were cloned from Brassica napus, and these genes could be induced by low temperature, ethylene, drought, high salinity, abscisic acid and jasmonate treatments. These four genes, named BnDREBIII-1 to BnDREBIII-4, were highly homologous and the 37th amino acid was the only difference among their ERF/ AP2 domains. BnDREBIII-1 was demonstrated to be able to bind to both dehydration-responsive element and the GCC box … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 32 publications
2
74
0
Order By: Relevance
“…It was already known that the AP2/ERF domain recognizes DNA through the conserved arginine and tryptophan residues located in 尾-sheets (Allen et al, 1998). Likewise, Ala-37 in the ERF domain plays an important role in the stability of the ERF domain and in the binding of the DRE element or GCC-box to the DNA (Liu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It was already known that the AP2/ERF domain recognizes DNA through the conserved arginine and tryptophan residues located in 尾-sheets (Allen et al, 1998). Likewise, Ala-37 in the ERF domain plays an important role in the stability of the ERF domain and in the binding of the DRE element or GCC-box to the DNA (Liu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The drnl-2 allele has a base substitution from C to T at position +278, resulting in an A to V substitution at amino acid 93. This conserved A residue has recently been shown in Brassica napus ERF/AP2 proteins to be essential for DNA binding (Liu et al, 2006), suggesting that the drnl-2 AP2 domain is unable to bind target genes. For the phv 899_CO2 allele, the insertion is after nucleotide +84.…”
Section: Drn Drnl and Phv Mutantsmentioning
confidence: 99%
“…PAS domains have been reported to mediate protein-protein interactions (Taylor and Zhulin, 1999;Card et al, than drnl-1. The mutated Ala residue has been shown in Brassica napus ERF/AP2 proteins to be essential for DNA binding (Liu et al, 2006), suggesting that the mutated drnl-2 protein is unable to bind target genes. Importantly, the penetrance of hypophysis or cotyledon phenotypes significantly increased in drn-1 drnl-1 double mutants, thereby demonstrating a role for DRN and DRNL in both the apical and basal domain of the Arabidopsis embryo and that the genes act redundantly.…”
Section: Drn and Drnl Form Heterodimers With Class III Hd-zip Proteinmentioning
confidence: 99%
“…A single amino acid substitution at Val14 by alanine or Glu19 by aspartic acid in the AP2 domain of DREB2A reduced the DNA binding activity and changed the DNA binding specificity of the protein (1). Liu et al reported that the GCC and DRE-binding ability of DREB1A and AtERF1 were reduced when Ala37 and Ala38 in the AP2 domain were mutated to Val (7).…”
Section: Introductionmentioning
confidence: 99%